Scope and mechanism of nitrile dihydroboration mediated by a β-diketiminate manganese hydride catalyst. Issue 28 (9th March 2020) - Nguyen, Thao T.; Kim, Jun-Hyeong; Kim, Suyeon; Oh, Changjin; Flores, Marco; Groy, Thomas L.; Baik, Mu-Hyun; Trovitch, Ryan J.
Abstract : Nitrile insertion allows for manganese-catalyzed nitrile dihydroboration at 80 °C. Abstract : The manganese hydride dimer, [( 2, 6-iPr2 Ph BDI)Mn(μ-H)]2, was found to mediate nitrile dihydroboration, rendering it the first manganese catalyst for this transformation. Stoichiometric experiments revealed that benzonitrile insertion affords [( 2, 6-iPr2 Ph BDI)Mn(μ-NCHC6 H5 )]2 en route to N, N -diborylamine formation. Density functional theory calculations reveal the precise mechanism and demonstrate that catalysis is promoted by monomeric species.